Different Approaches to Desing of the Group Traning in Adult Learning - Grabovska, Sofiia; Grebin, Nataliia; Karkovska, Ruslana (Journal of Education Culture and Society, 2021)
Aim. The aim of the study is a description of the types of training designs, based on various classification criteria and illustrated by examples from the authors’ own practice. Methods. We used theoretical analysis and synthesis of scientific information, as well as modelling the training structure. Results and Conclusions. It was proposed to classify the designs of group training, depending either on the internal logic of the teaching material or on the external organisation of the training. Regarding the logic of presentation certain designs, through the analysis of existing learning approaches, are proposed of training, based on different logic: presentation of information, assimilation of information, B. Bloom’s taxonomy, and competencies formation. Using these designs, it is possible to construct either the whole training or its separate parts (thematic blocks, exercises). The external organisation of the training includes design of the sum of exercises, or of a coherent story.